2019
DOI: 10.1002/hep.30222
|View full text |Cite
|
Sign up to set email alerts
|

Liver Complications Following Treatment of Hematologic Malignancy With Anti‐CD22‐Calicheamicin (Inotuzumab Ozogamicin)

Abstract: The frequencies of SOS and DILI after inotuzumab ozogamicin treatment were 1.5% and 7.9%, respectively, compared to none and 1% among controls who received standard chemotherapy. These data suggest that ADCs that do not target antigens present in the normal liver have a relatively low frequency of SOS but a relatively high frequency of DILI. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
(82 reference statements)
0
23
0
Order By: Relevance
“…Our analyses of factors increasing VOD risk were limited to some degree by small patient numbers; however, conditioning regimens containing dual alkylators, bilirubin levels greater than or equal to the upper limit of normal when tested before conditioning therapy or before follow‐up HSCT, and prior HSCT were associated with an increased risk of post‐HSCT VOD/SOS in the multivariate analysis, and an age ≥55 years and an increasing number of treatment cycles were associated with increased risk of post‐HSCT VOD/SOS in the univariate analysis. It is worth considering that, in this study, VOD was assessed by investigators, and a separate analysis of VOD events by an independent hepatic events adjudication board found that few of these events had a definite diagnosis . Nevertheless, as previously recognized, potential risk factors for the development of VOD/SOS must be carefully considered when one is making treatment decisions regarding InO, and procedures should be implemented to minimize the risk of post‐HSCT VOD/SOS, such as avoiding hepatotoxic conditioning agents.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our analyses of factors increasing VOD risk were limited to some degree by small patient numbers; however, conditioning regimens containing dual alkylators, bilirubin levels greater than or equal to the upper limit of normal when tested before conditioning therapy or before follow‐up HSCT, and prior HSCT were associated with an increased risk of post‐HSCT VOD/SOS in the multivariate analysis, and an age ≥55 years and an increasing number of treatment cycles were associated with increased risk of post‐HSCT VOD/SOS in the univariate analysis. It is worth considering that, in this study, VOD was assessed by investigators, and a separate analysis of VOD events by an independent hepatic events adjudication board found that few of these events had a definite diagnosis . Nevertheless, as previously recognized, potential risk factors for the development of VOD/SOS must be carefully considered when one is making treatment decisions regarding InO, and procedures should be implemented to minimize the risk of post‐HSCT VOD/SOS, such as avoiding hepatotoxic conditioning agents.…”
Section: Discussionmentioning
confidence: 91%
“…13 All potential VOD cases were reviewed by an independent hepatic events adjudication board, whose findings up to the March 2016 cutoff have been reported. 19 Hepatotoxic AEs were defined as described previously. 14 We coded AEs with the Medical Dictionary for Regulatory Activities (version 19.1), with toxicity graded according to the National Cancer Institute's Common Terminology Criteria for Adverse Events (version 3.0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic SOS/VOD developed in 22 (13%) of inotuzumab‐treated patients, but none in the standard of care cohort. HCT performed after inotuzumab exposure was associated with hepatic SOS/VOD in 17/77 (22%) of patients compared to only 3% (one of 32) if transplants were undertaken after standard therapy (McDonald et al , 2019). Recent studies suggest that antibody drug conjugates such as inotuzumab‐ozogamicin are taken up by LSECs, thereby inducing DILI, and that prior DILI is the critical factor associated with an increased risk of SOS/VOD following subsequent to HCT (McDonald et al , 1993).…”
Section: Risk Factors Associated With the Development Of Sos/vod Follmentioning
confidence: 99%